Calcined, rare earth modified hydrotalcite as a solid, reusable catalyst for dimethyl carbonate synthesis - Unnikrishnan, P.; Srinivas, D. (Industrial & Engineering Chemistry Research, 2012)
An eco-friendly building block and fuel additive dimethyl-carbonate (DMC)-was synthesized through a benign route by transesterification of propylene carbonate (PC) with methanol. The catalytic activity of a series of calcined, rare earth elements (La3+, Ce3+, Pr3+, Sm3+, and Y3+; 2-10 mol %) incorporated Mg-Al hydrotalcites (HT) was evaluated for this reaction. Among several, the La (8 mol %) modified HT showed the highest activity (PC conversion = 65.4 mol % and DMC selectivity = 88 mol % at 150 degrees C and in 2 h). Basicity of the catalyst played an important role on the transesterification activity. The influence of reaction parameters and calcination temperature on the catalytic activity of HT was investigated. The La modified HT catalyst was heterogeneous and could be reused with little loss of activity.

Highly active and reusable ternary oxide catalyst for dialkyl carbonates synthesis - Unnikrishnan, P.; Srinivas, D. (Journal of Molecular Catalysis A-Chemical, 2015)
The application of ternary oxides, prepared through calcination of rare-earth modified Mg/Al-hydrotalcite (HT), as highly active, selective, and reusable solid catalysts for dialkyl carbonates synthesis by transesterification reaction is reported. Dimethyl carbonate, for example, was prepared by reacting ethylene carbonate with methanol in 100 mol% selectivity at a yield of 95 mol%. Among several rare-earth modified precursors, La (10 mol%)-HT showed the highest activity. This catalyst was active even at ambient conditions. Basicity of the catalyst played crucial role on its performance. The activity of these catalysts was superior to the hitherto known solid catalysts for this reaction. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Dialkyl carbonate; Dimethyl carbonate (DMC); Rare-earth modified hydrotalcite; Solid base catalyst; Ternary oxide; Transesterification of cyclic carbonate

Direct synthesis of dimethyl carbonate from CO2 and methanol over CeO2 catalysts of different morphologies - Unnikrishnan, P.; Darbha, Srinivas (Journal of Chemical Sciences, 2016)
The direct synthesis of dimethyl carbonate (DMC) from carbon dioxide (CO2) and methanol is an attractive approach towards conversion of the greenhouse gas - CO2 into value-added chemicals and fuels. Ceria (CeO2) catalyzes this reaction. But the conversion efficiency of CeO2 is enhanced when the byproduct water in the reaction medium is separated by employing trapping agents like 2-cyanopyridine (2-CP). In this work, the influence of morphology of CeO2 on the direct synthesis of DMC in presence of 2-CP is reported. CeO2 catalysts of cube, rod, spindle and irregular morphology (Ce - C, Ce - R, Ce - S and Ce - N, respectively) were prepared, characterized and studied as catalysts in the said reaction conducted in a batch mode. Among all, Ce - S shows superior catalytic performance with nearly 100 mol% of DMC selectivity. Catalytic activity correlates with the concentration of acid and base sites of medium strength as well as defect sites. Ce - S has an optimum number of these active sites and thereby shows superior catalytic performance.
Keywords: acid-base catalysis; ceria; CO2 utilization; Dimethyl carbonate; influence of morphology

Heterogeneous catalysis - Unnikrishnan, P.; Srinivas, D. (Industrial catalytic processes for fine and specialty chemicals, 2016)
A majority of industrial catalytic processes use heterogeneous catalysts because of their engineering advantages. At present, heterogeneous catalysis covers almost 80% of the global market share. The demand for heterogeneous catalysis is growing annually. In 2010, it was about US 14 billion and expected estimation of it in 2015 is around 20 billion. Understanding at the molecular level the way surfaces of solids catalyze chemical reactions is a challenge in this area of research. This chapter introduces the fundamentals of heterogeneous catalysis, current industrial practices using solid catalysts, reaction steps involved in heterogeneous catalysis, conventional and advanced methods of catalyst preparation, catalyst characterization techniques, causes for catalyst deactivation, steps to avoid deactivation, and methods of catalyst reactivation.